The Influence of Promotion and Public Trust on the Decision to Use Loans - Adelvia, Siti; Indra Martini , Andi; Halim , Abdul (Golden Ratio of Social Science and Education, 2024)
The objectives of this study are: 1. To determine the effect of promotion and public trust partially on the decision to use loans at PT. Pegadaian Mamuju Branch. 2. To determine the effect of promotion and public trust simultaneously on the decision to use loans at PT. Pegadaian Mamuju Branch. This research is a quantitative study with two independent variables and one dependent variable with the test tools to be used, namely 1) validity test, 2) reliability test, 3) multiple linear regression test, t test (partial) and f test (simultaneous). The sample used in this study was 98 respondents. Processing of research data using multiple linear regression with SPSS version 24.0 software tools to read the direction of the influence of the independent variable on the dependent variable partially t test and f test. The results showed that promotion has a partially significant effect on the decision to use loans at PT. Pegadaian Mamuju Branch. Consumer trust has a partially significant effect on the decision to use loans at PT. Pegadaian Mamuju Branch. The results also show that promotion and public trust have a significant effect simultaneously on the decision to use loans at PT. Pegadaian Mamuju Branch.